1982
DOI: 10.1002/1097-4679(198201)38:1<142::aid-jclp2270380123>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Depression and self-actualization in gifted adolescents

Abstract: Administered the Multiscore Depression Inventory and the Personal Orientation Inventory to 248 academically gifted adolescents drawn from across the state of South Carolina to participate in a select program. Low but significant correlations were noted among several of the scales. Factor analysis of the scales of both instruments resulted in five factors for females and six for males. In both samples the first two factors accounted for more than half the variance. Gifted students who were not self‐actualizing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
2
1

Year Published

1984
1984
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 12 publications
1
9
2
1
Order By: Relevance
“…In view of the present findings supporting the notion that gifted students have significantly more positive social-emotional characteristics than their non-gifted peers in terms of internalizing symptoms, it is difficult to explain why several previous investigations have produced the opposite finding (e.g., Berndt, et al, 1982;Hayes & Sloat, 1989Kline & Short, 1991). Perhaps findings in many of the studies in this general area are sample-dependent.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…In view of the present findings supporting the notion that gifted students have significantly more positive social-emotional characteristics than their non-gifted peers in terms of internalizing symptoms, it is difficult to explain why several previous investigations have produced the opposite finding (e.g., Berndt, et al, 1982;Hayes & Sloat, 1989Kline & Short, 1991). Perhaps findings in many of the studies in this general area are sample-dependent.…”
Section: Discussioncontrasting
confidence: 89%
“…These findings may indicate a certain sensitivity or vulnerability to depression and other internalizing disorders which have been described by other researchers (Hayes & Sloat, 1989;Kline & Short, 1991). Some researchers have reported that gifted children tend to be more socially introverted (Berndt, Kaiser, & Van Aalst, 1982) and that they often prefer to be left alone or joined by a single friend rather than participate in larger and more social groups of peers (Terman, 1925). Additionally, the possible heightened sensitivity gifted children may experience may leave them much more aware of their peers' reactions to errors in a social setting, which may increase anxiety and hinder social development (Hayes & Sloat, 1990).…”
mentioning
confidence: 99%
“…In a study by Berndt, Kaiser, and van Aalst (1982), it was noted that a subgroup of gifted adolescents appeared to have the adolescent equivalent of a "success depression," some prominent symptoms being guilt, low self-esteem, helplessness and cognitive difficulty. The gifted sample as a whole was more depressed than their adolescent peers, as measured by the Multiscore Depression Inventory (Berndt, Petzel & Berndt, 1980).…”
Section: Studying Adjustment Needsmentioning
confidence: 99%
“…Several studies have been conducted in an attempt to determine the level of psychological adjustment in gifted children. Anxiety, depression, suicide and delinquency were among the most specific and important variables to be investigated as they are known to correlate with psychological health (Baker, 1995;Bartell & Reynolds, 1986;Berndt, Kaiser, & Van Aalst, 1982;Janos, Marwood & Robinson, 1985;Parker, 1996).…”
Section: Introductionmentioning
confidence: 99%